Potensi Rhizobium dalam Meningkatan Efisiensi Fiksasi Nitrogen untuk Kesuburan Tanah : Kajian Literatur - Indah Cahyani Zega; Natalia Kristiani Lase (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Soil fertility is an important element in agricultural sustainability, especially in supporting plant growth. One natural way to increase soil fertility is through Biological Nitrogen Fixation (FNB) by Rhizobium bacteria. These bacteria have a symbiotic relationship with legume plants, forming root nodules that convert atmospheric nitrogen into compounds that plants can absorb, such as ammonium (NH4+). The purpose of this article study is to determine the potential of Rhizobium bacteria in increasing and efficiency of nitrogen fixation which has an impact on soil fertility and increasing plant productivity. This study adopts a library research method or approach, which involves a series of systematic activities, starting from collecting data through various library sources, reading in depth, recording important information, to processing the research materials. The study results show that Rhizobium can reduce dependence on chemical fertilizers, increase soil fertility, and produce growth hormones that support nutrient absorption. These findings emphasize the important role of Rhizobium in supporting sustainable agriculture, especially in tropical regions where access to synthetic fertilizers is minimal.